THE METHOD OF IMPROVING PHYSICAL AND SPECIAL PHYSICAL FITNESS INDICATORS OF SHORT-DISTANCE RUNNERS - Kazakov, Rokhilla (Журнал иностранных языков и лингвистики, 2023)
The present article is devoted to the optimization of training loads, improving morphological indications by direct distributions of special preparation loads and general preparation of highly qualified runners who can run for short distance.